The Development of Siyasah Maliyah in Enhancing Community Welfare through MSMEs - Syam, Syafruddin; Permata, Cahaya (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2024)
Micro, Small, and Medium Enterprises (MSMEs) play a vital role in enhancing community welfare, necessitating the development of siyasah maliyah (economic governance). This requires central and regional governments to establish policies that involve non-governmental institutions such as the Indonesian Ulema Council (MUI) and Mosque Prosperity Boards (BKM) in MSME development to improve societal welfare. This study aims to examine the role of MSMEs in promoting welfare, understand and elaborate on the synergy between MUI and BKM in MSME development, and analyze the siyasah maliyah concept concerning their roles in welfare enhancement through MSMEs. Utilizing doctrinal research with conceptual and statutory approaches, legal materials were gathered through document studies, then processed, analyzed, and qualitatively described. The findings reveal that MUI and BKM can synergize effectively in developing MSMEs, with six forms of synergy identified: coordinative, consultative, resolutive, enlightening, empowering, and socializing. Both institutions significantly contribute to empowering the Muslim community's economy and improving welfare through MSME initiatives. The government must formulate policies as part of siyasah maliyah development, engaging non-governmental institutions like MUI and BKM in fostering MSMEs. Such efforts are critical to ensure government policies on welfare improvement address not only income growth and fiscal management but also community empowerment and collaboration with non-governmental entities to bolster MSME growth and enhance public welfare comprehensively.